Multiagent Systems in Travel Planning - Rodrigues, Diego Fialho; Amaral, Heber; Oliveira, Alcione de Paiva; Costa, Simone Dornelas (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
Currently, as a result of globalization and other factors, the tourism market has remained high. Assisting the customer in order to satisfy their desires and constraints is a major challenge in this sector. This paper presents an agent-based system for developing a travel plan. In the system, according to the preferences informed by tourists, several agents cooperate in order to construct the travel plan that best suits the client needs. A tourism domain ontology was developed to enable communication between the agents. The system relies on the assistance of the greedy algorithm to trace the routes. A heuristic function was designed to ensure the fulfillment of the customer goals.